ANALISIS KESESUAIAN FUNGSI KAWASAN HUTAN LINDUNG PADA KESATUAN PENGELOLAAN HUTAN LINDUNG (KPHL) TEPO ASA AROA DI KECAMATAN PETASIA KABUPATEN MOROWALI UTARA - P, Alfran Pranata; Hamzari, Hamzari (Universitas Tadulako, 2020)
In the designation of the functions of the forest area established by the government needs to be held a review, so it is clear the designation of the functions of the forest area that needs to be protected and which may be utilized by the results. In relation to this it requires a conformity analysis of the forest area's functions using the latest data, namely large scale and current conditions. Such data can be analyzed using the Geographic Information System (GIS). Geographic Information System (GIS) is a computer-based system useful in performing mapping (mapping) and analyzing various things and events that occur above the Earth's surface. GIS is very precisely used as an analytical tool in helping determine the function of protected forest areas on KPHL Tepo Asa Aroa in Kecamatan Petasia, northern Morowali County, Central Sulawesi Province. In this study, the methods used were forays (overlay) and scores. The outtake (overlay) and score are enforced against maps of marbles, maps of soil types, and precipitation maps to gain conformity of the protected forest area's function in Petasia Subdistrict, North Morowali County, Central Sulawesi Province. Of the result of the forest area's function scoring there is a mismatch of the 20.412.96 Ha forest area's forest function, the area of production forest is 7.934.21 Ha, and the area of limited production forest is 12.478.75 Ha, so remaining area of protected forest area is 823.25 Ha. It is in effect some factors namely class of marbles, soil type and rainfall intensity.Keywords : Forest protected, forest area, forest area Score